Different Responses of Soil Bacterial Communities to Nitrogen Addition in Moss Crust - Huang, Tingwen; Liu, Weiguo; Long, Xi-En; Jia, Yangyang; Wang, Xiyuan; Chen, Yinguang (Frontiers in Microbiology, 2021)
Bacterial communities in soil serve an important role in controlling terrestrial biogeochemical cycles and ecosystem processes. Increased nitrogen (N) deposition in Northwest China is generating quantifiable changes in many elements of the desert environment, but the impacts of N deposition, as well as seasonal variations, on soil bacterial community composition and structure are poorly understood. We used high-throughput sequencing of bacterial 16S rRNA genes from Gurbantünggüt Desert moss crust soils to study the impacts of N addition on soil bacterial communities in March, May, and November. In November, we discovered that the OTU richness and diversity of soil bacterial community dropped linearly with increasing N input. In November and March, the diversity of the soil bacterial community decreased significantly in the medium-N and high-N treatments. In May, N addition caused a substantial change in the makeup of the soil bacterial composition, while the impacts were far less apparent in November and March. Furthermore, the relative abundance of major bacterial phyla reacted nonlinearly to N addition, with high-N additions decreasing the relative richness of Proteobacteria, Bacteroidetes, and Acidobacteria while increasing the relative abundance of Actinobacteria and Chloroflexi. We also discovered that seasonality, as characterized by changes in soil moisture, pH, SOC, and AK content, had a significant impact on soil bacterial communities. Significant variations in the makeup of the community were discovered at the phylum and genus levels throughout the various months. In May, the variety of soil bacterial community was at its peak. Further investigation showed that the decrease in soil bacterial diversity was mostly attributed to a drop in soil pH. These results indicated that the impact of N deposition on the soil bacterial community was seasonally dependent, suggesting that future research should evaluate more than one sample season at the same time.